The Influence of Rubberwood Biochar Size on the Effectiveness of Using Urea Fertilizer in the Cultivation of Pakcoy (Brassica chinensis L.) - Haryanto, Agus; Mudita, Nyoman Arif; Waluyo, sri; Triyono, Sugeng (Jurnal Agricultural Biosystem Engineering, 2023)
The effectiveness of fertilizer and crop production can be increased through the provision of biochar as a soil amendment. This research aims to evaluate the effect of the combination of varying sizes of rubber wood biochar with doses of urea fertilizer on the growth of pak choy mustard plants. The research was conducted with two factors arranged in a completely randomized design. The first factor is the size of the rubber wood biochar and the second factor is the dose of Urea fertilizer, each consisting of 4 levels. All treatment combinations were carried out with 3 repetitions. The response variables observed include soil pH, plant height, number of leaves, canopy area, and fresh plant production. The results showed biochar size factor had a significant effect on soil pH and fresh weight. The urea fertilizer dosage factor shows a significant influence on the plant height and fresh weight. The treatment with the most optimal growth was 1 mm biochar produced yield of 19.03 g/plant, while Urea dose of 2 g/plant produced pak choy plants of 20.72 g/plant. Keywords: Biochar, Pakchoy, rubberwood, size, Urea.